2022
DOI: 10.1159/000520617
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Resuscitation Practices in Europe: A Survey of the Union of European Neonatal and Perinatal Societies

Abstract: <b><i>Background:</i></b> We aimed to evaluate the policies and practices about neonatal resuscitation in a large sample of European hospitals. <b><i>Methods:</i></b> This was a cross-sectional electronic survey. A 91-item questionnaire focusing on the current delivery room practices in neonatal resuscitation domains was individually sent to the directors of 730 European neonatal facilities or (in 5 countries) made available as a Web-based link. A comparison was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…22 A recent survey from Europe identified many resuscitation practices aligned with the international newborn resuscitation guideline, however large variation in practice continued to occur. 23 The current survey identifies differences in practices after adjusting for the continent and the income status groups for the lowest GA of infants resuscitated. Future research and quality improvement activities will bridge the gap in knowledge on the influence of bundles of best practices for stabilisation on clinical outcomes, especially for infants born at 22–23 weeks GA.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent survey from Europe identified many resuscitation practices aligned with the international newborn resuscitation guideline, however large variation in practice continued to occur. 23 The current survey identifies differences in practices after adjusting for the continent and the income status groups for the lowest GA of infants resuscitated. Future research and quality improvement activities will bridge the gap in knowledge on the influence of bundles of best practices for stabilisation on clinical outcomes, especially for infants born at 22–23 weeks GA.…”
Section: Discussionmentioning
confidence: 99%
“…A more supportive ILCOR recommendation giving equal prominence to LMA and FM was recently published online 34. Nonetheless, a recent European survey on neonatal resuscitation showed that, among the hospitals declared to have the availability of the LMA in their delivery ward, only 4 out of 476 (1%) participants indicated the LMA as the first choice for administer PPV to a neonate at birth 35…”
Section: Discussionmentioning
confidence: 99%
“…This Turkish study is part of a European survey on delivery room practices endorsed by the Union of European Neonatal and Perinatal Societies (UENPS) and the Turkish Neonatal Society. 6 The study was approved by the Padua Provincial Institutional Review Board and declared as not meeting the criteria for human subject research.…”
Section: Methodsmentioning
confidence: 99%